1. To solve this problem you need to apply the formula for calculate the surface area of a square pyramid, which is shown belown:
A=2bs+b^2
A is the surface area of the square pyramid.
b is lenght of the base of the square pyramid.
s is the slant height of the square pyramid.
2. Then, you have:
b=2.7 inches
s=2.5
3. When you substitute the values above into the formula for calculate the surface area of the square pyramid, you obtain:
A=2bs+b^2
A=2(2.7 inches)(2.5 inches)+(2.7 inches)^2
A=13.5 inches^2+7.29 inches^2
A=20.79 inches^2
The answer is: 20.79 inches^2